Prevalencia de Anticonceptivos estudio realizado en los barrios de Democracia. y Cascayunga - Rioja - Región San Martín Periodo 1992 - Castro Piña, Yusbith (1993)
The issue of women's health is closely related to program planning, family fertility, education, employment status, access to health services among others, but what to study in our environment is necessary. In general, developed countries are engaged in the search for new strategies in order to increase the availability of services and family planning products in a responsible parenthood optics allowing them freely and consciously determine the number of children, ensuring a quality of life acceptable (adequate nutrition, housing education and employment status). Recent national studies (4) reveal an average decrease of demographic variations, which to be investigated locally are still stubbornly high, indicators affecting morbidity and maternal and infant mortality. The increased use of modern contraceptive methods is still slow in 1986 was 28 percent, figures in 1992 reached 33.5 percent. Internationally Colombia shows the highest figures, 66 percent; Bolivia, 24 percent; Ecuador, 29 percent; Venezuela, 32 percent; being higher demand in urban areas than rural areas. The importance of determining the prevalence of contraceptive use in a disaggregated manner is vital, since it will develop strategies for individual and group type in regional areas that are considered high economic growth; hence the need to develop the present study.